USING TWO DIFFERENT PROMOTERS OF LYSOSTAPHIN GENE TO CHANGE PROTEIN PRODUCTION - Jalal Y. Mustafa (Basrah Journal of Veterinary Research)
Bacteriocins are bacterial antimicrobial peptides with bactericidal activity against other bacteria. Staphylococcins are bacteriocins produced by staphylococci, which are gram-positive bacteria with medical and veterinary importance. In this study we are using two promoters from two plasmids to lysostaphin gene to change production of lysostaphin protein then killed Staphylococcus aureus and compared with pBluescript plasmid as control, pTrc99a get increased the production of lysostaphin protein while the pBAD30 are decreased the production in compared with pBluescript plasmid as control, at the same time both plasmid reported succeeded to lysostaphin expression and gave the protein with different concentration.